A controlled sustained release system of anti-inflammatory drugs based on nanofiber materials
The preparation of nanofiber carrier materials with electrical-strain dual stimulation responses through electrospinning method solves the problems of low efficiency in the preparation of nanoparticles and vesicles and low drug release efficiency in the prior art, and achieves uniform, continuous and efficient drug release efficiency.
Patent Information
- Application Number
- CN202111262885.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-28
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2041-10-28
AI Technical Summary
The preparation efficiency of existing nanoparticles and vesicles is low, the process is complex, the drug release efficiency is low, and traditional drug administration methods have toxic side effects and inconvenience.
Electrospinning method is used to prepare long-acting controlled sustained-release nanofiber carrier materials with double stimulation response. The dual release of drugs is achieved by adding conductive bodies such as silver nitrate and graphene oxide to polyurethane fibers, combined with anti-inflammatory drugs such as methylprednisolone.
The uniform and continuous release of drugs is achieved, the drug release efficiency is improved, the toxic side effects are reduced, and the drug delivery efficiency is provided is more convenient.
Smart Images

Figure CN114010794B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of material preparation, and relates to a controlled sustained-release system of anti-inflammatory drugs based on nanofiber materials, and in particular to an electric-strain dual stimulation responsive long-acting controlled sustained-release nanofiber carrier material and a preparation method thereof. Background Art
[0002] 1. Commonly used biomaterials for drug release:
[0003] With the development of material technology, more and more biomaterials are applied to drug delivery systems (DDS) to improve the targeting and water solubility of drugs, reduce the toxic and side effects of drugs, improve the therapeutic efficacy of drugs, and ultimately reduce the pain of patients. Polymer materials are usually used as carrier materials for drug-loaded release systems. According to their different degradation properties, they can be divided into biodegradable materials and non-degradable materials. Biodegradable systems have received great attention and development in the field of drug release, while non-degradable materials have developed slowly due to the need to be recovered or further processed after being introduced into the human body. Polyesters and polyester polymers are usually used as controlled release materials. For degradable materials, although the content of the drug gradually decreases over time, the rate of release will also decrease, but the release rate of the drug can be increased by the degradation of the matrix, so that the drug is released at a constant rate.
[0004] Polyester is the best biodegradable and most widely studied system. Polyester has been widely used in drug release systems as a biomaterial with good performance. It has better compatibility. Polymers are derived from monomers of their own metabolites, so the degradation of these materials produces corresponding hydroxy acids that are safe when used in vivo. Natural biodegradable materials have a long history in medicine, dating back more than 3,000 years, when the ancient Egyptians used plant fibers, hair, and wool as suture materials. The need to develop safer biodegradable sutures and improve commonly used sutures has put higher demands on synthetic biodegradable polymer materials. In the 1960s and 1970s, PGA, PLA, and PLGA were developed as degradable sutures. Since then, due to their good compatibility and degradation characteristics, they can be decomposed in the body to produce non-toxic natural byproducts such as water and carbon dioxide, and are easily eliminated, which makes their application in drug release prominent. Although much of the pioneering work in controlled release systems has been done using non-degradable polymers, degradable and biodegradable polymers are a better choice for developing polymer drug release systems.
[0005] Polyhydroxybutyrate (PHB) is a biodegradable, non-toxic, biocompatible polymer. This polymer obtained from nature is suitable for use in the field of biomedicine. Due to its appropriate compatibility and controllable degradation, it is currently the most promising biomedical material. We combine PHB with other biopolymers to produce a drug release system to study drug diffusion kinetics. Polylactic acid (PLLA) is widely used in various biomedicines due to its biodegradability, compatibility and outstanding mechanical properties. Therefore, we combine PHB and PLLA to produce a new drug release system.
[0006] The unresolved issues of polymer drug delivery systems include low efficiency in preparing nanoparticles and vesicles, complex processes, and low drug release efficiency.
[0007] 2. Commonly used fiber materials for drug release
[0008] Natural and synthetic polymer materials are often used as drug carriers to improve the efficiency of drug release systems. Using silk fibroin (SF) and polyethylene oxide (PEO) with good biocompatibility and biodegradability as electrospun materials, water as solvent, and different mixing ratios, electrospun beaded fiber materials with adjustable bead morphology and size were obtained under certain spinning conditions. The release behavior of the anti-tumor drug doxorubicin hydrochloride under different conditions was studied. The results showed that the electrospun beaded fiber material released the drug more slowly and lasted longer, and the drug sustained release effect was better than that of the electrospun smooth fiber material. The conditions for preparing coaxial beaded fiber materials by coaxial electrospinning were also explored, and their drug sustained release behavior was studied. The results showed that the drug sustained release ability of SF / PEO coaxial beaded fiber materials was significantly better than that of beaded fiber materials and smooth fiber materials. The prepared materials have potential application value in the fields of biomedicine and filtration.
[0009] Some studies have mixed natural polymer CS, synthetic polymer and inorganic tetraethyl orthosilicate (TEOS), used electrospinning technology, and utilized the characteristics of each substance. By adjusting the concentration and ratio of each substance, the conditions were optimized to obtain the best ratio, and a drug-loaded fiber membrane with a certain specific surface area and a certain porosity was synthesized. The drug was added to the spinning solution with the best ratio to obtain a drug-loaded composite fiber membrane, and the effects of different drug contents on the composite fiber membrane and the sustained release performance of the fiber were discussed. The specific contents are as follows: 1. Using polyamide (PA) / chitosan (CS) / tetraethyl orthosilicate (TEOS) as raw materials, the composite fiber membrane was synthesized by electrospinning technology. By adjusting the various parameters in the spinning blend, the optimal ratio was determined to be 1:0.13:0.67; different concentrations of ofloxacin (OFLO) drugs were added to the spinning solution with the best ratio for in vitro release. The study found that when the drug content was 0.2%, the fiber sustained release performance was the best, and the cumulative release amount reached 71%. 2. Replace the high molecular polymer with polyvinyl alcohol, use polyvinyl alcohol (PVA) / chitosan (CS) / tetraethyl orthosilicate (TEOS) as raw materials, and use electrospinning technology to synthesize composite fiber membranes. By adjusting various parameters in the spinning blend to optimize the spinning conditions, the optimal ratio is determined to be 1:0.43:1.2; the fiber membrane has a certain specific surface area (7.805m2 / g) and a narrow pore structure. Different concentrations of ofloxacin (OFLO) drugs were added to the spinning solution with the best ratio for in vitro release. The study found that the prepared fiber membrane has a certain sustained release effect, and the cumulative release amount reaches 69%.
[0010] There are also studies that use water as a solvent and use the electrospinning method to prepare polyvinyl alcohol (PVA) ultrafine fiber membranes. Aspirin and bovine serum albumin can be loaded into PVA ultrafine fibers by electrospinning to make PVA ultrafine fiber membranes with drug release function. After the ultrafine fiber membrane is placed in physiological saline, aspirin and bovine serum albumin in the fiber are released at a faster rate. Compared with the cast membrane containing the same amount of drugs, the release kinetic curve is significantly different.
[0011] 3. Electrospinning drug delivery method
[0012] The drug soaking method is to first prepare an electrospun nanofiber mat, and then soak the fiber mat in a drug solution or a solution of drug-loaded nanoparticles to allow the drug to be adsorbed into the fiber mat. The drug soaking method can achieve a sudden release of the drug in the initial stage, and then slowly and continuously release the drug. The overall sustained release effect is better than direct administration, and it has significant effects in postoperative anti-infection, antibacterial and anti-inflammatory aspects. KHATSEE et al. prepared polylactic acid (PLA) and polybutylene adipate-terephthalate (PBAT) fiber mats to achieve a sudden release effect, and the drug-loaded PLA / PBAT fiber mat has antibacterial activity and can be used as a carrier for anti-infection drugs. Wei Xiaohui et al. used electrospinning technology to prepare polyethersulfone nanofiber mats, and composited nano-MgO particles with the prepared polyethersulfone nanofiber mats to improve the efficiency of the use of nano-MgO powder.
[0013] The co-encapsulation method mainly mixes polymer solution with drugs or drug-loaded nanoparticles to prepare drug-loaded electrospun nanofibers. The drugs are more evenly distributed inside the fibers. Compared with the drug-immersion method, the drug burst release phenomenon is improved and the sustained release effect is better. ADEPU et al. loaded cellulose acetate (CA) with a low half-life drug diclofenac sodium to prepare drug-loaded electrospun nanofibers, which can effectively prevent the initial burst release of diclofenac sodium and lay the foundation for the controlled diffusion of low half-life drugs. MORGANE et al. prepared hyaluronic acid (HA) nanofibers by electrospinning, added polyvinyl alcohol (PVA) as a carrier polymer and embedded hydroxypropyl-β-cyclodextrin, used the in situ cross-linking process of the scaffold to ensure non-toxicity, and selected the non-steroidal anti-inflammatory drug naproxen (NAP) as a model drug. The results showed that the model drug had good sustained release performance on the scaffold fiber, which provided a basis for the application of wound dressings with sustained release characteristics of anti-inflammatory drugs.
[0014] Coaxial electrospinning is to make the solution of drugs or drug-loaded nanoparticles and polymers enter two concentric spinneret pipes to prepare composite nanofibers with a core-shell structure. Compared with the co-encapsulation method, it has a stronger sustained release effect and a larger drug loading capacity. Li Rongjun et al. used zein and L-polylactic acid (PLLA) to prepare a new type of nanofiber material using coaxial electrospinning technology, combining bone-inducing conductive growth factors with bone conduction, reducing the risk of infection and enhancing surgical safety.
[0015] Emulsion electrospinning is to prepare the drug and polymer solution into an emulsion and electrospin to prepare a core-shell composite nanofiber. Compared with coaxial electrospinning, emulsion electrospinning has better controllability and a wider range of applications. It is of special significance in the preparation of fibers containing active substances, special drugs and other functions. However, in the process of emulsion preparation, the addition of substances such as surfactants may affect the biocompatibility of drugs. Cui Yin et al. prepared carboplatin fiber membranes using carboplatin aqueous solution as the aqueous phase, PLLA dichloromethane solution as the oil phase, and Poloxamer 188 as an emulsifier. Studies have shown that when the mass fraction of Poloxamer 188 is 10%, 20% and 30%, the sustained release time exceeds 10h. The release curve of Poloxamer 188 conforms to the Freundlich equation, and the release curve of carboplatin conforms to the 0-order release kinetics. Emulsion electrospinning can produce carboplatin fiber membranes with sustained release and He La cell inhibition.
[0016] 4. Electrospun nanofiber anti-inflammatory drugs
[0017] Methylprednisolone (MP), corticosteroids (HC) and flumethasone (Dx), as well as nonsteroidal anti-inflammatory drugs (NSAIDs) such as indomethacin, ibuprofen and aspirin, are widely used in myocardial infarction. Glucocorticoids are effective in establishing inflammatory responses, thereby inhibiting the transduction of inflammatory mediators, reducing the expression of chemokines, promoting the clearance of apoptotic cells, and inducing macrophages to form an anti-inflammatory phenotype.
[0018] Methylprednisolone (MP) has been proposed to reduce inflammation, decrease myocardial damage and collagen deposition, and increase capillary density in experimental models of myocardial infarction. Furthermore, the effects of methylprednisolone depend on the superior access, treatment dose, and duration. For example, glucocorticoid treatment is considered a risk factor for heart failure and high-dose methylprednisolone can lead to luminal dilation and thinning of the infarct cavity. Local delivery of small molecules using a biomaterial carrier has the advantage of sustained release with simple systemic administration compared to local injection with a saline carrier. Bio-based polymers with irritant responses have broad application prospects in various fields because of their excellent properties and advantages, especially in controlled drug release.
[0019] Small molecule anti-inflammatory drugs include naturally extracted and synthetic drugs. Synthetic drugs with anti-inflammatory effects include non-steroidal aspirin, analgin and acetaminophen, and steroidal dexamethasone, cortisone and glucocorticoid drugs, which have certain anti-inflammatory and immunosuppressive effects, but these drugs generally have the risk of increasing the burden on the digestive and urinary systems when taken for a long time, leading to diseases such as kidney tissue atrophy, allergies, and gastrointestinal ulcers.
[0020] 5. Methods for achieving controlled sustained release
[0021] Compared with the traditional drug delivery process, the drug sustained-release system has the advantages of reducing the number of drug administrations, reducing the toxic and side effects of drugs on the body, and prolonging the drug's action time in the body. Drug-loaded fibers made of degradable biopolymer materials have the characteristics of large specific surface area, more pore structure, and good mechanical properties, which are of great significance to the development of drug delivery, tissue engineering, biomedicine and other fields. Therefore, in order to further expand the application of fibers in drug sustained-release carriers, it is of certain research significance to develop a drug-loaded fiber material with sustained-release properties. Electrospinning technology is a simple and easy-to-operate method for preparing fibers. The prepared fibers have the characteristics of controllable size, high porosity, and large specific surface area. They are widely used in drug release materials, tissue engineering, adsorption experiments and other fields.
[0022] Solution electrospinning has been widely used in the preparation of controlled drug release systems. It can obtain nanofibers in a simple, low-cost and controllable manner, and has the advantages of being able to use a variety of materials and having a small fiber diameter. In addition, this technology is very convenient because these fibers can be coated on any non-woven fabric and ordered fiber surface. However, for drug release systems, solution electrospinning often requires toxic solvents to dissolve drugs and carriers, which may not only affect the activity of the drugs, but also cause certain harm to people during the spinning process, and this solvent often cannot be completely volatilized during the spinning process. In the biomedical field, the residual solvents in these fibers have certain toxic effects on cells and tissues.
[0023] It is worth noting that melt electrospinning can obtain polymer fibers in a solvent-free manner, which can provide a safe and environmentally friendly process and will not destroy the activity of the drug. Therefore, the disadvantages of solution electrospinning, such as expensive solvent recovery costs, the risk of solvent explosion and solvent residues, can be avoided. Diffusion-based drug release mainly occurs in non-degradable release systems. However, for degradable materials, they usually have unstable chemical bonds and may be affected by hydrolysis reactions, especially the self-catalytic reaction mechanism of terminal functional groups. In this regard, despite impressive technical achievements in the preparation of ultrafine fibers, there is only limited work to study the diffusion and hydrolysis problems of fiber materials during drug release. Obviously, these problems require us to conduct comprehensive experimental and theoretical tests. In order to solve the problem of intrinsic diffusion dynamics, it is necessary to measure the amount of drug controlled release from macroscopic fiber membranes under different intrinsic conditions. For drugs that are poorly soluble or insoluble in water, they have a low solubility after taking, so it is difficult for the body to absorb. Not only does it cause a waste of drugs, but it also fails to achieve the expected effect.
[0024] Researchers have tried to improve its dissolution rate through different methods, but there are few studies on improving dissolution rate through ultrafine fibers. Nanofibers produced by electrospinning have high specific surface area, small fiber diameter, and mainly amorphous structure, which are conducive to drug dissolution. Therefore, drugs can be prepared into fibers through carriers to increase drug dissolution and improve its bioavailability.
[0025] Usually, the concentration of drugs taken into the human body will rise sharply to the maximum, and the concentration of drugs will quickly decrease after being decomposed and excreted by the human body. Therefore, it is difficult to keep the drugs in the human body at the therapeutic level for a long time. Traditional drug administration methods cannot directly produce effects on the lesion site and will have toxic side effects on tissues and organs. Traditional drug administration methods require multiple administrations, which brings great inconvenience to patients. Traditional drug administration methods usually require an injection every 6 hours, and the drug concentration will have a large fluctuation range. Excessive drug concentration will be toxic to the human body and cause physical harm. Too low drug concentration will reduce the effect of the drug and fail to achieve the purpose of treatment. Drugs can only have a therapeutic effect in a very short time.
[0026] Different nanofiber carrier materials achieve different in vitro drug releases. Methylprednisolone, as a classic anti-inflammatory drug, has a strong anti-inflammatory effect, just like attaching an anti-inflammatory drug to a wound. However, it requires long-term stable and slow release to achieve a more ideal clinical efficacy. Therefore, achieving the determination of the in vitro release of methylprednisolone is the focus of the drug-carrying preparation process. The present invention introduces anti-inflammatory drugs (especially MP) into a drug controlled release system based on conductive polymers, and provides an electric-strain dual stimulation response long-acting controlled sustained-release nanofiber carrier material. The system shows a good drug release pattern, has adjustability, stability and accurate quantitative administration, and provides good conditions for long-term drug supply. Summary of the invention
[0027] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and provide a controlled sustained-release system for anti-inflammatory drugs based on nanofiber materials, introduce anti-inflammatory drugs such as MP into a drug controlled-release system based on conductive polymers, and prepare a long-acting controllable sustained-release nanofiber carrier material with dual electrical-strain stimulation response.
[0028] The present invention adopts the following technical solution:
[0029] A controlled sustained-release system for anti-inflammatory drugs based on nanofiber materials is a nanofiber material with dual electrical-strain stimulus responsiveness obtained by using polyurethane (PU) as solute, N,N-dimethylformamide (DMF) and tetrahydrofuran (THF) as solvents, and adding a conductor and anti-inflammatory drugs.
[0030] The conductor may be one or more of metal salts (such as silver nitrate), graphene oxide, carbon nanotubes, polyaniline, polypyrrole, polythiophene and derivatives thereof.
[0031] The anti-inflammatory drug is usually one or more of methylprednisolone (MP), cortisone (HC) and flumethasone (Dx).
[0032] Furthermore, the nanofiber material is prepared by electrospinning, and the electrospinning parameters are: a spinning distance of 10 to 15 cm, a liquid supply rate of 0.5 to 2 mL / h, a drum speed of 250 to 300 rad / min, a voltage of 10 to 20 kV, a temperature of 25 to 40° C., and a humidity of less than 35%.
[0033] Furthermore, the conductor is preferably silver nitrate and graphene oxide, the anti-inflammatory drug is MP, and the raw materials of the system are calculated by weight:
[0034]
[0035] Furthermore, the diameter of the prepared nanofibers is 480-814 nm.
[0036] The drug-loading and releasing efficiency of the system is above 98.89%.
[0037] The present invention uses polyurethane as the raw material of the drug release system, and by adding an electrical conductor and an anti-inflammatory drug, a long-acting controllable drug sustained-release system having both an electric-strain dual stimulation response can be obtained, which has less side effects and high safety compared with traditional drug dosage forms. The rapid release process of part of the drug can be first realized in a short time, the drug release rate is faster, inflammation is effectively controlled, and then the slow and continuous release of the drug is realized, achieving the purpose of the "double release" of the drug. Especially when silver nitrate and graphene oxide are used as electrical conductors to add to the system, methylprednisolone (MP) is used as the anti-inflammatory drug, it can be realized that under the condition of electrical stimulation and good elastic deformation, the drug-loaded release time becomes longer, the release rate becomes more uniform, and the drug-loaded release efficiency can reach 98.89%.
[0038] The beneficial effects of the present invention are:
[0039] The method of the present invention has simple process and strong operability. The prepared nanofiber carrier material can be a flexible film and has excellent electrical conductivity, mechanical properties, wet stability and biocompatibility. In addition, under the condition of electrical stimulation and good elastic deformation, the drug release time is long and the release speed is uniform. It can be seen from the cumulative release curve of MP that the release efficiency can eventually reach more than 98%. The nanofiber material has a broad application prospect and can be applied to drug release systems, bone tissue repair, treatment of nerve damage, cardiovascular diseases, tissue engineering scaffolds, medical excipients, bioeffectors, biosensors and the like. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is a scanning electron microscope photograph (1000 times) of the nanofiber material prepared in Example 3.
[0041] Figure 2 is the standard curve of methylprednisolone (MP).
[0042] Figure 3 It is a schematic diagram of the relationship between the cumulative release amount of MP in the nanofiber carrier materials prepared in Example 1, Example 2, and Example 3 and time. DETAILED DESCRIPTION
[0043] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and specific examples. Since the effect of anti-inflammatory drugs is related to the concentration and dosage of the drugs used, methylprednisolone (molecular formula C 22 H 30 O5, molecular weight 374.47) with a purity of 98% to illustrate the effect, which is also applicable to other anti-inflammatory drugs.
[0044] Example 1
[0045] Polyurethane (PU) and methylprednisolone (MP) were used as raw materials for electrospinning, and N,N-dimethylformamide (DMF) and tetrahydrofuran (THF) were used as solvents.
[0046] Components calculated by weight:
[0047]
[0048] The solvent is N,N-dimethylformamide (DMF) and tetrahydrofuran (THF) in a ratio of 1:1.
[0049] Weigh DMF / THF (1 / 1) = 4.725g on an electronic balance as a solvent and place it in a clean glass stirring bottle. Weigh 0.5g of PU and place it in a glass stirring bottle. Stir at 60°C in a digital temperature-controlled heating stirrer for 3 hours to completely dissolve the PU and finally obtain a uniform and stable spinning solution. Then perform electrospinning to prepare nanofiber materials loaded with MP. The electrospinning parameters are: temperature of 40.0°C, humidity of 23.1%, spinneret distance of 11cm, liquid supply rate of 2mL / h, slide speed of 15mm / s, drum speed of 300rad / min, and voltage of 15kV.
[0050] The average diameter of the prepared flexible nanofiber carrier material is 250nm, the average thickness is 0.14mm, and the air permeability is 884.30mm / s. Since the water droplets stay on the surface of the nanofibers, the contact angle test shows that the material is hydrophilic. The tensile stress and strain are 327674Pa and 169% respectively.
[0051] The prepared nanofiber carrier material has a low drug release efficiency when only elastically deformed, and the cumulative release curve of MP shows that the release efficiency finally reaches more than 88.62%. In this embodiment, because no conductor is added, the prepared nanofiber carrier material cannot generate electrical stimulation, so the drug release efficiency is not high.
[0052] Example 2
[0053] Polyurethane (PU), silver nitrate (AgNO3), and methylprednisolone (MP) are used as raw materials for electrospinning, and N,N-dimethylformamide (DMF) and tetrahydrofuran (THF) are used as solvents. Components calculated by weight:
[0054]
[0055] The solvent is N,N-dimethylformamide (DMF) and tetrahydrofuran (THF) in a ratio of 1:1. Use an electronic balance to weigh DMF / THF (1 / 1) = 4.7g as a solvent and place it in a clean glass stirring bottle. Then weigh 0.05g of AgNO3 and 0.5g of PU and put them in a glass stirring bottle. Stir at 60°C for 3 hours in a digital temperature-controlled heating stirrer to completely dissolve PU and finally obtain a uniform and stable spinning solution. Electrospinning is performed to prepare nanofiber materials loaded with MP. The electrospinning parameters are: temperature of 40.0°C, humidity of 23.1%, spinneret distance of 11cm, liquid supply rate of 2mL / h, slide speed of 15mm / s, roller speed of 300rad / min, and voltage of 15kV.
[0056] The average diameter of the prepared nanofiber carrier material is 750nm, the average thickness is 0.14mm, and the air permeability is 1512.71mm / s. Since the water droplets stay on the surface of the nanofibers, the contact angle test shows that the material is hydrophilic. The tensile stress and strain are 559875Pa and 126% respectively.
[0057] The prepared nanofiber carrier material has improved drug release efficiency under the condition of elastic deformation and the action of a single conductor (silver nitrate). From the cumulative release curve of MP, it can be seen that the release efficiency finally reaches more than 96.38%. In this embodiment, because a single conductor is added, the prepared nanofiber carrier material can be partially electrically stimulated, and the drug release efficiency is significantly improved.
[0058] Example 3
[0059] Polyurethane (PU), silver nitrate (AgNO3), graphene oxide (GO), and methylprednisolone (MP) are used as raw materials for electrospinning, and N,N-dimethylformamide (DMF) and tetrahydrofuran (THF) are used as solvents. Components calculated by weight:
[0060]
[0061]
[0062] The solvent is N,N-dimethylformamide (DMF) and tetrahydrofuran (THF) in a ratio of 1:1. Use an electronic balance to weigh DMF / THF (1 / 1) = 4.6895g as a solvent and place it in a clean glass stirring bottle. Then weigh 0.05g of AgNO3 and 0.003g of GO and put them in a glass stirring bottle. Then put the glass bottle into an ultrasonic cleaner and ultrasonicate for 60 minutes to make GO completely dispersed in the solution. Then add 0.5g of PU, and the total mass of the spinning solution is 10g. Stir at 60℃ for 3 hours in a digital temperature-controlled heating stirrer to completely dissolve PU and finally obtain a uniform and stable spinning solution. Prepare nanofiber carrier materials by electrospinning. The electrospinning parameters were as follows: temperature of 40.0°C, humidity of 23.1%, spinneret distance of 11 cm, liquid supply rate of 2 mL / h, slide speed of 15 mm / s, drum speed of 300 rad / min, and voltage of 15 kV.
[0063] The average diameter of the prepared nanofiber material is 710nm, the average thickness is 0.19mm, and the air permeability is 1358.13mm / s. Since the water droplets stay on the surface of the nanofiber, it can be known from the contact angle test that the material is hydrophilic. The tensile stress and strain are 462139Pa and 149% respectively. The electrical signal is tested with a DM3068 digital multimeter. When the prepared nanofiber material is laid flat, the voltage fluctuates up and down with 0.0076mV as the node, when stretched by 10%, the voltage fluctuates up and down with 0.0029mV as the node, and when stretched by 20%, the voltage fluctuates up and down with 0.0086mV as the node.
[0064] When the prepared nanofiber carrier material is subjected to elastic deformation and the action of multiple conductors (silver nitrate and graphene oxide), silver nitrate and graphene oxide work together to conduct electricity; polyurethane meets the strain requirement of elastic deformation. From the release curve, it can be seen that under the dual stimulation of electrical stimulation and elastic strain, the drug release efficiency is greatly improved, and the release efficiency can eventually reach more than 98.89%. In this embodiment, because multiple conductors are added, the prepared nanofiber carrier material can produce relatively strong electrical stimulation, and the drug release efficiency is further improved. This shows that under the dual stimulation of electricity and strain, the drug release effect is good.
[0065] It can be seen that the nanofiber carrier material prepared by the present invention has good elastic deformation and good electrical conductivity. The drug release of the nanofiber carrier material is studied. According to the cumulative release curve of the drug, it can be seen that the drug release efficiency of the nanofiber carrier material without the addition of a conductor is only 88.62%. After the conductor is added, the material has electrical stimulation and good elastic deformation, the drug release time becomes longer, the release rate becomes more uniform, and the drug release efficiency can even reach more than 98.89%. The material can generate a stable and fluctuating electrical stimulation signal, providing a more extensive and reliable experimental basis for stimulation therapy. In addition, the preparation method is simple and highly operable, and the prepared nanofiber carrier material has excellent mechanical properties, electrical conductivity and biocompatibility.
[0066] Studies have shown that endogenous electric fields are widely present in organisms and play an important role in tissue growth and wound healing. External artificial electric fields can have a significant impact on cell morphology, cell migration, cell proliferation, cytokine secretion, etc., especially electrical stimulation. The electrical stimulation signal is related to the growth rate, regeneration ability, and differentiation of cells in a specific direction. The present invention simultaneously adds conductive substances and anti-inflammatory drugs, and after generating electrical stimulation signals of arbitrary frequency and amplitude, provides a more extensive and reliable experimental basis for stimulation therapy. The electrical stimulation can also promote the growth of cells and the formation of new tissues. Therefore, a kind of electric-strain dual stimulation response long-acting controllable slow-release nanofiber carrier material of the present invention has a good application prospect. Controlling the release of drug loading under electrical stimulation reduces the secondary injury of surgery and can accelerate wound healing. The nanofiber material has a broader application prospect and can be applied to aspects such as drug release system, bone tissue repair, treatment of nerve damage, cardiovascular disease, tissue engineering scaffold, medical auxiliary material, bioeffector, and biosensor.
Claims
1. A controlled sustained release system of anti-inflammatory drugs based on nanofiber materials, characterized in that: The system is prepared by using polyurethane PU as solute, N,N-dimethylformamide DMF and tetrahydrofuran THF as solvent, and then adding a conductor and an anti-inflammatory drug; the nanofiber material is prepared by electrostatic spinning; the conductor uses silver nitrate AgNO3 and graphene oxide GO, and the anti-inflammatory drug is methylprednisolone MP. The raw materials of the system are calculated by weight: PU 3~5 parts; Silver nitrate 0.21~ 0.50 parts; Graphene oxide 0.01-0.03 parts; MP 0.3~ 0.5 parts; DMF 46.985~48.500 copies; THF 46.985~48.500 parts; The diameter of the nanofiber is 480-814 nm; the drug release efficiency of the system is above 98.89%.